PAPARAN MIKROBA PADA BUBUR BAYI SEHAT DI KOTA SEMARANG - Wijayanti, Hartanti Sandi; Kurniawati, Nur Indah; Margawati, Ani; Fitranti, Deny Yudi; Ayustaningwarno, Fitriyono; Afifah, Diana Nur (Journal of Nutrition College, 2023)
ABSTRACTBackground: Healthy Baby Porridge is a term usually used for ready-to-eat complementary food products sold on the roadside. These products were great in demand and were chosen by consumers for cheap and practical reasons. However, the safety of these products was not recognized yet.Objectives: This study aimed to determine the total microbial value of Healthy Baby Porridges based on storage condition and to detect Escherichia coli and Salmonella bacteria.Methods: This study was quantitative descriptive research. The samples tested consisted of porridges and steamed rice. The total microbial value was assessed by using Total Plate Count (TPC), and the presences of Escherichia coli and Salmonella were identified. The TPC was performed for three conditions: (1) soon after samples were purchased at room temperature (26.5 - 27 °C), and after stored for six hours: (2) at room temperature, and (3) in the refrigerator (5°C). Escherichia coli and Salmonella was identified immediately after samples were purchased.Results: The TPC value soon after purchase ranged from 1.7 x 102 to 2.7 x 104. After six hours stored, it was between 1.4 x 103 to 1.9 x 107 at room temperature and between 4.8 x 102 to 1.3 x 106 in the refrigerator. The samples contained no Escherichia coli and Salmonella.Conclusion: The total microbial value of Healthy Baby Porridges had already exceeded the maximum limit of 1 x 102 soon after purchase and increased with storage time, especially at room temperature. Escherichia coli and Salmonella were not found. Consuming products with total microbial value above the threshold can potentially pose a health risk.  Keywords: Healthy Baby Porridges; complementary food; Total Plate Count; Salmonella; Escherichia coliABSTRAKLatar belakang: Bubur Bayi Sehat merupakan istilah yang biasa digunakan untuk produk Makanan Pendamping ASI siap santap yang dijual oleh pedagang kaki lima di pinggir jalan.  Bubur Bayi Sehat diminati karena alasan praktis dan murah. Akan tetapi, belum diketahui bagaimana keamanan pangan produk tersebut dari cemaran mikrobiologis. Tujuan: Penelitian ini bertujuan untuk menganalisis total mikroba Bubur Bayi Sehat pada beberapa kondisi penyimpanan, serta mengetahui keberadaan bakteri Escherichia coli dan Salmonella.Metode: Penelitian ini merupakan penelitian deskriptif kuantitatif. Sampel yang diuji berupa bubur dan nasi tim. Total mikroba diukur dengan metode Angka Lempeng Total (ALT), dan keberadaan Escherichia coli dan Salmonella diidentifikasi. Uji ALT dilakukan pada tiga kondisi yaitu (1) saat awal produk dibeli pada suhu ruang 26,5 – 27 °C, dan setelah produk disimpan enam jam: (2) di suhu ruang dan (3) di kulkas suhu 5°C. Identifikasi Escherichia coli dan Salmonella dilakukan segera setelah pembelian.Hasil: Nilai ALT saat awal produk dibeli berkisar antara 1,7 x 102 – 2,7 x 104. Setelah enam jam disimpan, nilainya berkisar antara 1,4 x 103 – 1,9 x 107 pada suhu ruang, dan antara 4,8 x 102 – 1,3 x 106 di kulkas. Sampel negatif mengandung Escherichia coli dan Salmonella.Simpulan: Nilai ALT mikroba pada Bubur Bayi Sehat sejak awal sudah melebihi batas maksimum 1 x 102 dan meningkat seiring lama penyimpanan, terutama pada suhu ruang. Escherichia coli dan Salmonella tidak ditemukan. Mengonsumsi produk dengan total mikroba di atas ambang batas dapat berpotensi menimbulkan risiko kesehatan.Kata Kunci: Bubur Bayi Sehat; MPASI; Angka Lempeng Total mikroba, Salmonella; Escherichia coli